1980
DOI: 10.1128/aem.39.4.818-822.1980
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of spices on growth and toxin production of toxigenic fungi

Abstract: The inhibitory effects of 29 commercial powdered spices on the growth and toxin production of three species of toxigenic Aspergillus were observed by introducing these materials into culture media for mycotoxin production. Of the 29 samples tested, cloves, star anise seeds, and allspice completely inhibited the fungal growth, whereas most of the others inhibited only the toxin production. Eugenol extracted from cloves and thymol from thyme caused complete inhibition of the growth of both Aspergillus flavus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
4

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(67 citation statements)
references
References 25 publications
3
58
0
4
Order By: Relevance
“…The active fraction is probably responsible for the antimicrobial activity of the oil. The effectiveness of O. saccatum on the growth of the tested microorganisms is probably effects (Hitokoto et al 1980;Deans and Svoboda 1990;Akgül et al 1991). The extent of inhibition of tested microorganism growth was dependent on the concentrations of essential oil used.…”
Section: Resultsmentioning
confidence: 99%
“…The active fraction is probably responsible for the antimicrobial activity of the oil. The effectiveness of O. saccatum on the growth of the tested microorganisms is probably effects (Hitokoto et al 1980;Deans and Svoboda 1990;Akgül et al 1991). The extent of inhibition of tested microorganism growth was dependent on the concentrations of essential oil used.…”
Section: Resultsmentioning
confidence: 99%
“…EO against P. citrinum, and the potential of the EO for controlling fungal spoilage of cheese. Different EOs have been used as natural inhibitors of fungal growth and mycotoxin production during recent decades, and their phenolic compounds have a fundamental role (Bullerman 1974;Hitkoto et al 1980;Benjilali et al 1984;Basilico and Basilico 1999;Beatriz et al 2001;Burt 2004;Nguefack et al 2004.;Omidbeygi et al 2006;Rasooli et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…How the ancients obtained their knowledge we do not know, but modern research has shown that many of their ideas are valid. Scientific experiments on the antimicrobial properties of spices, herbs and their components have been documented in the late 19th Century and interest continues to the present (Corran and Edgar 1933;Fabian et al 1939;Webb and Tanner 1945;Dold and Knapp 1948;Maruzzella and Freundlich 1959;Beuchat 1976;Zaika and Kissinger 1979;Hitokoto et al 1980;Mabrouk and El-Shayeb 1980;Shelef et al 1980;Azzouz and Bullerman 1982;Ueda et al 1982;Zaika et al 1983;Deibel and Banwart 1984). It was also recognized quite early that the antiseptic power of spices and herbs resides in the essential oils and in some cases can be attributed Red Yepppr Ginger the strongest inhibitors for a variety of microorganisms.…”
Section: Introductionmentioning
confidence: 99%